Spectrometric registration of x-ray and gamma radiation by detecting modules “silicon planar detector - scintillator” - Bochek, G.L.; Kapliy, А.A.; Kiprich, S.K.; Kovalenko, G.D.; Maslov, N.I.; Ovchinnik, V.D.; Semisalov, I.L.; Shirokopetlev, F.O.; Shlyahov, I.N.; Shulika, M.Yu.; Vasiliev, G.P.; Yalovenko, V.I. (Problems of Atomic Science and Technology, 2022)
The use of detection modules based on a silicon planar uncooled detector and a scintillator in combination with readout electronics makes it possible to create detection complexes for spectrometric detection of X-ray and gamma radiation in various fields of research, including nuclear physics, nuclear power engineering, high-energy physics, medicine, etc. The results of a study of detection complexes with silicon detectors with an active area of 2×2 and 5×5 mm and cesium iodide scintillators doped with thallium in the energy range from 50 keV to 0.662 MeV are presented. Використання детектуючих модулів на основі кремнієвого планарного неохолоджуваного детектора і сцинтилятора в поєднанні з реєструючою електронікою дозволяє створювати комплекси для спектрометричної реєстрації рентгенівського і гамма-випромінювання в різних областях досліджень, включаючи ядерну фізику, ядерну енергетику та інші дослідження детектуючих комплексів з кремнієвими детекторами і активною площею розміром 2×2 та 5×5 мм та сцинтиляторами з іодиду цезію, легованого талієм, у діапазоні енергії 50 кеВ…0,662 МеВ.